1993
DOI: 10.1016/0378-1097(93)90581-l
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence of the gene coding for Clostridium barati type F neurotoxin: Comparison with other clostridial neurotoxins

Abstract: The neurotoxin gene from Clostridium barati ATCC43756 was cloned as a series of overlapping polymerase chain reaction (PCR) generated fragments using primers designed to conserve toxin sequences previously published. The toxin gene has an open reading frame (ORF) of 1268 amino acids giving a calculated molecular mass of 141,049 Da. The sequence identity between the C. barati ATCC43756 and non-proteolytic C. botulinum 202F neurotoxins is 64.2% for the light chain and 73.6% for the heavy chain. This is much lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…These facts may explain the apparent neutralization of C. baratii toxin F by both C. botulinum antitoxins E and F while confirming the partial sequence uniqueness of the C. baratii toxin F. This structural difference is further supported by studies showing that it requires more type F botulinal antitoxin to neutralize a given amount of C. baratii toxin F than it does to neutralize botulinal toxin F and that C. baratii toxin F is more susceptible to cross-neutralization by type E antitoxin (7). The partial sequence uniqueness of C. baratii toxin F is in contrast to the sequence identities found between the light and heavy chains of C. butyricum toxin E and those of C. botulinum toxin E, 96 and 98.1% homology, respectively (13).…”
Section: Vol 40 2002 Notes 2261mentioning
confidence: 82%
See 2 more Smart Citations
“…These facts may explain the apparent neutralization of C. baratii toxin F by both C. botulinum antitoxins E and F while confirming the partial sequence uniqueness of the C. baratii toxin F. This structural difference is further supported by studies showing that it requires more type F botulinal antitoxin to neutralize a given amount of C. baratii toxin F than it does to neutralize botulinal toxin F and that C. baratii toxin F is more susceptible to cross-neutralization by type E antitoxin (7). The partial sequence uniqueness of C. baratii toxin F is in contrast to the sequence identities found between the light and heavy chains of C. butyricum toxin E and those of C. botulinum toxin E, 96 and 98.1% homology, respectively (13).…”
Section: Vol 40 2002 Notes 2261mentioning
confidence: 82%
“…Recently, there have been several studies on the genetic and structural relationships among clostridial neurotoxins (5,8,9,13). Sequence analysis has shown that there is high genetic homology between the toxins E produced by C. butyricum and C. botulinum but low relatedness between the genes coding for the toxins F of C. baratii and saccharolytic C. botulinum.…”
Section: Vol 40 2002 Notes 2261mentioning
confidence: 99%
See 1 more Smart Citation
“…Botulinum neurotoxins are produced by host bacterial cells in the form of single polypeptide chains, which are about 1500 amino acid residues in length (Mr~150 kDa) (Binz et al, 1990; East et al, 1992; Hauser et al, 1990; Poulet et al, 1992; Thompson et al, 1993). A single molecule of each toxin possesses three functional domains: receptor-recognizing, transport and catalytic.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it has been difficult to construct Clostridium strains that produce derivatives of neurotoxins and other proteins. Genes for all eight clostridial neurotoxins have been cloned, and their sequences have been identified (2,6,9,18,30,31). Many attempts to express fragments of clostridial neurotoxins in Escherichia coli have failed because of the unusually high AT content of clostridial DNA.…”
mentioning
confidence: 99%